(untitled) (Afaq Lughawiyyah, 2024)
The primary function of language is to serve society in various ways, a role similarly fulfilled by Arabic literature, including Nigerian Arabic literature, which encompasses both national and global issues. The COVID-19 pandemic is one such issue that has garnered the attention of Nigerian poets, who have channeled their literary energies into this topic, albeit with varied perspectives. This paper examines the terminology related to COVID-19 in Nigerian Arabic poetry from the year 2020, exploring the poets’ ability to coin new terms for the pandemic. Notably, these terms were developed individually across different environments, even before the global community established standard terminology. The study employs inductive and analytical methods and reveals that Arabic studies in Nigeria are progressing significantly, in tandem with the development of Arabic literature. This progression underscores the need for a dominant body to oversee new linguistic issues, providing modern terminology to writers and scholars of Arabic studies, akin to the role of historical linguistics in addressing communicative changes that occur within a language during specific periods and in specific environments.